What drives people to purchase virtual gifts in live streaming? The mediating role of flow - Li, Boying; Hou, Fangfang; Guan, Zhengzhi; Chong, Alain Yee-Loong (2018)
Live streaming, a new form of social media, is growing explosively due to its real-time interaction and new monetization model. Considering its popularity and unique features, it is important to gain a theoretical understanding of live streaming. Yet limited attention has been paid to it. This research investigates what factors may affect people’s consumption intention of virtual gifts in live streaming from contextual and personal dimensions. Based on flow theory, this study also explores the mediating role of flow and the moderating role of gender. The theoretical framework is tested using Structural Equation Modeling based on survey data collected in China. The study contributes to flow theory by highlighting the importance of flow in mediating the effects of interactivity, social presence, curiosity and social media dependence on consumption intention of virtual gifts. It also reveals gender differences in the influence of flow on consumption intention of virtual gifts.